(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The idea of using asymmetric tooth forms has gained momentum in gearing design. Similar to symmetric basic rack gears, tooth action parameters are established in the first stage. The second stage involves calculating the unified generating basic rack for a set of mated gears. In some cases, it is possible to determine the features of specific fundamental rack tooth profiles for each gear in a transmission. Gearings with asymmetrical profiles have the advantage of having a higher-pressure angle than operational profiles (as a result of a lower pressure angle than non-operating profiles) and the possibility for a considerable improvement in the face contact ratio. In this study, symmetric and asymmetric tooth profiles will be compared using the finite element analysis tool Ansys. Asymmetric (different pressure angle) and symmetric (different pressure angle) tooth profiles will be designed and built in the 3D modelling software CATIA. The designs made with different materials will go through structural examination (mild steel and EN 32 steel).